2013
DOI: 10.12934/jkpmhn.2013.22.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Childhood Trauma on Post-traumatic Stress Symptoms and Dissociation: Mediating Effect of Bullying

Abstract: The purposes of the study were to determine whether specific forms of childhood traumatic experience predicts post traumatic stress symptoms and dissociation and to investigate the mediating effects of bullying experience on forms of childhood trauma and post traumatic stress symptoms or dissociation. Methods: Participants were patients (n=90) from "S" clinic for psychological trauma. Data were collected from January 2012 to January 2013 through semi-structured interviews and self-reports using a modified Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In line with evidence suggesting that dissociation is a common sequela of adverse and/or traumatic life experiences, many empirical studies have demonstrated that individuals with SMIs exposed to childhood adversity (e.g. sexual abuse, physical abuse, emotional abuse, neglect, bullying), experience greater dissociation compared to individuals exposed to little or no trauma . However, the relationship between childhood trauma and dissociation in individuals with SMIs remains contradictory, as some studies have found no association between the two constructs .…”
Section: Introductionmentioning
confidence: 95%
“…In line with evidence suggesting that dissociation is a common sequela of adverse and/or traumatic life experiences, many empirical studies have demonstrated that individuals with SMIs exposed to childhood adversity (e.g. sexual abuse, physical abuse, emotional abuse, neglect, bullying), experience greater dissociation compared to individuals exposed to little or no trauma . However, the relationship between childhood trauma and dissociation in individuals with SMIs remains contradictory, as some studies have found no association between the two constructs .…”
Section: Introductionmentioning
confidence: 95%